Analysing profitability and its determinants in Maharatna enterprises in India: a panel data approach. (12th August 2020) - Singh, Krishna; Sur, Debasish
The present paper attempts to analyse the profitability of the 'Maharatna' CPSEs in India using panel data analysis approach during the period 2002 to 2014. Return on capital employed (ROCE) was used in this study as the profitability measure. The study revealed a wide variation in the level of profitability across the Maharatna companies. The stationarity of the ROCE was checked through four types of panel unit root tests. The results obtained in these tests showed that the data of ROCE in all the Maharatna companies were stationary in nature. A fixed effect regression model was applied in analysing the determinants of profitability of the Maharatna companies.